Karst Land System and Sustainable Development - Bai, Xiaoyong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint encompasses karst ecosystem quality, ecosystem services, climate change, ecological restoration, vegetation dynamics, land management, and the element biogeochemical cycle. These are closely related to land system science, landscape, land-climate interactions, the water-energy-land-food nexus, ecosystem services, and multifunctionality and sustainability. We expect that this reprint will contribute to ecological construction and land use management in karst areas.